Optically stimulated luminescence and spectral emission features of radioluminescence and thermoluminescence of natural kunzite. (November 2020) - Alatishe, M.A.; Ogundare, F.O.; Folley, D.E.; Chithambo, M.L.; Chikwembani, S.
Abstract: Features of luminescence optically stimulated from natural kunzite using 470 nm blue light are reported. Preparatory measurements of its X-ray excited radioluminescence and thermoluminescence show that the sample has two main bands centered at 360 nm and 600 nm. The optically stimulated luminescence discussed in this report was monitored in the UV region and is presumed to be the same 360 nm emission that appears in the radioluminescence and thermoluminescence spectra. The glow curve shows at least three peaks at 74, 202, 432 o C for heating at 1 o C and the third one is a composite of two. Only the first two peaks are deduced to contribute most of the optically stimulated luminescence. Highlights: OSL of kunzite is mostly from the contributions of its first two TL peaks. The time to stimulate about 90% and 95% of the sample's OSL signal are 500 and 1000 s respectively. RL spectrum shows two emission bands centered at 360 nm and 600 nm.